Synthesis and photocatalytic activity of p–n junction CeO2/Co3O4 photocatalyst for the removal of various dyes from wastewater. (27th April 2018) - Tang, Yuanzheng; Zhang, Meng; Wu, Zhengying; Chen, Zhigang; Liu, Chengbao; Lin, Yun; Chen, Feng
Abstract: CeO2, Co3 O4, and Co3 O4 /CeO2 composites are successfully synthesized by a simple coprecipitation method. X-ray powder diffraction (XRD) and Fourier transform infrared (FTIR) results indicate that the CeO2, Co3 O4, and Co3 O4 /CeO2 precursors sintered at 500 °C has good crystallization. The cerium nitrate introduced into cobalt nitrate precursor solution improved the surface morphology and photocatalytic activity of Co3 O4 significantly. The photo-degradation of methylene blue (MB), xylenol orange (XO), methyl orange (MO), and methyl red (MR) catalyzed by prepared nanocomposites were studied under visible light irradiation. Photocatalytic experiment results indicate that the photocatalytic activity of Co3 O4 /CeO2 composites for degradation of various dyes highly depend on pH value. The optimum conditions for the photocatalytic experiments of Co3 O4 /CeO2 composites were determined to be as follows: dye concentration, 50 mg L −1, and catalyst concentration, 50 mg L −1 . The excellent photocatalytic activity of the p–n junction Co3 O4 /CeO2 composites can be ascribed to the ·O 2− radicals and h + .